PEMBELAJARAN TEKS CERPEN MENGGUNAKAN MEDIA ANIMASI BERBASIS THINK TALK WRITE - Fitri Agustina; Indra Permana; Heri Isnaini (Parole : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
Quality, innovative, and applied learning media can increase motivation and activation learn learners. Thus, the research this time USES a think talk write based animation medium. The think talk write model makes the learner more active in building his knowledge through reading, thinking, discussing, and interpreting. The study aims to describe students' responses to the think talk write based media animation. The study USES qualitative descriptive methods in the form of case study conducted at SMA Karya Pembangunan Cikalongwetan. The data collection consists of observation of responses and direct interaction with learners. Studies have proven that the clever text study using animated media collaborated with the think talk write model makes learners more active and able to understand the stories theoretically and empirical.Â